The Tail at Scale. - DEAN, JEFFREY; BARROSO, LUIZ ANDRÉ (Communications of the ACM, 2013)
The article discusses high-latency episodes in large online services and tail-tolerant software techniques that form a predictable whole out of less-predictable parts to reduce the episodes' effect on whole-system performance. The article notes variability in latency distribution or response time to user actions can be reduced by parallelization of sub-operations across different machines. Topics include system utilization that avoids overprovisioning, performance variability, and the Google search engine.